Diagnostics Provides Determination of the Technical Condition and Mechanisms of the Rolling Stock (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The trouble-free operation of all objects of locomotive mechanisms and electric motors can ensure a safe transportation process on railway transport. Diagnostic tools form the basis of train safety. Diagnostics ensures the determination of the technical condition of all devices and mechanisms of the rolling stock. With the help of diagnostics, the tasks of not only managing the transportation process are solved, but also the physical condition of the object is determined, as well as their malfunction.